IKY Award "Mobility and Scholarship Fund" - Markou, George (My University, 2026)
Scholarship from the State Scholarship Foundation (I.K.Y. Ίδρυμα Κρατικών Υποτροφιών Ελλάδος), through a special financial support "Mobility and Scholarship Fund" of Greece
Keywords: Sciences